BenR, a XylS Homologue, Regulates Three Different Pathways of Aromatic Acid Degradation in Pseudomonas putida - Cowles, Charles E. (American Society for Microbiology, 2000)
Pseudomonas putida converts benzoate to catechol using two enzymes that are encoded on the chromosome and whose expression is induced by benzoate. Benzoate also binds to the regulator XylS to induce expression of the TOL (toluene degradation) plasmid-encoded meta pathway operon for benzoate and methylbenzoate degradation. Finally, benzoate represses the ability of P. putida to transport 4-hydroxybenzoate (4-HBA) by preventing transcription of pcaK, the gene encoding the 4-HBA permease. Here we identified a gene, benR, as a regulator of benzoate, methylbenzoate, and 4-HBA degradation genes. A benR mutant isolated by random transposon mutagenesis was unable to grow on benzoate. The deduced amino acid sequence of BenR showed high similarity (62% identity) to the sequence of XylS, a member of the AraC family of regulators. An additional seven genes located adjacent to benR were inferred to be involved in benzoate degradation based on their deduced amino acid sequences. The benABC genes likely encode benzoate dioxygenase, and benD likely encodes 2-hydro-1,2-dihydroxybenzoate dehydrogenase. benK and benF were assigned functions as a benzoate permease and porin, respectively. The possible function of a final gene, benE, is not known. benR activated expression of a benA-lacZ reporter fusion in response to benzoate. It also activated expression of a meta cleavage operon promoter-lacZ fusion inserted in an E. coli chromosome. Third, benR was required for benzoate-mediated repression of pcaK-lacZ fusion expression. The benA promoter region contains a direct repeat sequence that matches the XylS binding site previously defined for the meta cleavage operon promoter. It is likely that BenR binds to the promoter region of chromosomal benzoate degradation genes and plasmid-encoded methylbenzoate degradation genes to activate gene expression in response to benzoate. The action of BenR in repressing 4-HBA uptake is probably indirect.